ENGLISH LITERATURE, FOLK TRADITIONS AND ENGLISH BALLADS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article talks about English literature, English folk traditions and ballads. Also, the history of folk traditions and the comparison of the national values of the English people with Uzbek traditions are mentioned. In addition, the following examples of traditions and ballads will help you better understand this topic.